The Impact of Going Circular: A Financial Analysis of Circular Economy Models for Profitability in the ICT Sector - Sydnei Murphy Creel; Nurul Wardhani; Aspiansyah (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
This study explores the impact of community-based restorative justice (RJ) programs on youth offenders by employing a qualitative comparative case study method. Data were collected through semi-structured interviews, program documents, and observation notes involving participants, facilitators, and community stakeholders. The research investigates how RJ practices influence youth behavior, accountability, recidivism, and reintegration into society. Thematic analysis was conducted to identify recurring patterns in participant experiences and program outcomes. Results show that RJ programs promote emotional healing, reduce recidivism, and strengthen youth-community relations through direct victim-offender engagement and community support mechanisms. Findings highlight the importance of facilitator training, victim involvement, and early intervention in maximizing program effectiveness. The study concludes that restorative justice is a viable and impactful alternative to punitive juvenile systems, offering youth meaningful paths to reform and reconciliation.